Chapel Project: Replica of the first temple of the Presbyterian Church of Brazil in Londrina – PR - Caires, Carla; Riviera, Julia Morais (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 40 No especial (2024): Prêmio Reynaldo Camargo Neves 2024 e Bolsa Fundação Araucária, 2024)
The Chapel Project of the Architecture and Urbanism course at the Philadelphia University Center (UniFil) is based on research and investigations of fundamental information and practical proposals in order to preserve the historical and architectural memory of the Presbyterian Church of Brazil in the city of Londrina, Paraná . According to historical data, the first temple of the Presbyterian Church of Brazil was erected in 1936, in the first years of the formation of the city of Londrina, the temple underwent an expansion in 1940, and was demolished in 1954. The architectural study of the construction techniques used to build the pioneer temple, is fundamental for understanding the beginning of the city's development and the use of wood as the main raw material, as local material resources were used in order to obtain economy, speed and ease for carpenters and immigrants at that time. The replica of the temple of the Presbyterian Church of Brazil on a smaller scale is one of the segments worked on in this project. To this end, a site survey was carried out to collect information about the physical characteristics of the land provided by IPB Central de Londrina and, based on the measurements and raw materials described in documentary references, the executive project and its three-dimensional modeling were designed using software in the most faithful way possible to the 1940 temple. In addition to recovering the architectural characteristics of the first temple in its volume, the proposed use for the replica is a small museum in order to value the memory of the IPB pioneers in the city and preserve the church history for future generations. Finally, it is also part of the Capela Project, the ebook that is under development in order to describe in in-depth detail the process of historical research and other work carried out by the Capela Project, such as the creation of the physical model of the first temple.